Dopant Effect and Cell-Configuration-Dependent Dielectric Properties of Nematic Liquid Crystals. (13th May 2013) - Lin, Feng-Ching; Wu, Po-Chang; Jian, Bo-Ru; Lee, Wei
Abstract : The dielectric polarizations induced by impurity ions in both high- and low-resistivity nematic liquid crystals (NLCs) were investigated. Upon adding carbon nanotubes (CNTs) as a dopant, the former showed no distinct change in the low-frequency (< 10 2 Hz) dielectric spectrum, whereas the latter exhibited dramatic decrease in dielectric constant in that the CNTs remarkably trapped the impurity ions in the NLC of high ionic content. Consequently, the dopant raised the voltage holding ratio by 26% and prolonged the lifetime of the cell. Also investigated were ionic behaviors in the low-resistivity NLC confined in cells with three different configurations. The diffusion constant of the ions in homeotropic cells was found to be the greatest, and the dc conductivity, determined by the diffusion constant, was also higher in the homeotropic ones.